Toleransi Beberapa Genotipe Padi Umur Pendek terhadap Pasokan Air Terbatas - Yamin, Mohamad; Suprihatno, B.; Rustiati, Tita; Sitaresmi, Trias (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2012)
Field and screen house experiments were conducted in 2009 in Indramayu and Sukamandi. The field experiments was carried out at farmerâs field in the Cilandak village, Anjatan District, Indramayu Regency from May to October 2009. Nine rice genotypes (AS996, OM5240, BP5478-2F-KN-11-2-B, Inpari 10, Inpari 1, Silugonggo, dan Dodokan) were tested. The experiment was arranged in a randomized block design with three replications. The treatments were: (a) fully irrigated (100% irrigated); (b) half-dry (75% irrigated), irrigation water was given until one month after planting, followed with weekly irrigation until crop harvest, and (c) dry (50% irrigated), irrigation water was given until one month after planting, then no more irrigation was given until harvest. The plant characters observed were: percentage of empty grain per panicle, grain weight per unit area, drought sensitivity index (S), and genotype superiority index (Pi). The screenhouse experiment was conducted in pots at the Rice Research Institute, Sukamandi, from July to October 2009, arranged in a completely randomized block design with three replications. The rice genotypes tested were the same as those in the field trial, The treatments wer three categories of water supply, namely minimum (4,000 m3/ha/season), optimal (5,500 m3/ha/season) and excessive (7,000 m3/ha/season). The plant characters observed were: grain weight (g/pot), percentage of filled grains/panicle, plant height, and age of flowering. The results showed that water stress during flowering stage increased percentage of empty grains from 25.6% to 34.3% and decreased grain yields from 11.3% to 23.2%. Genotypes AS996, OM5240, and BP5478-2F-KN-11-2-B were tolerant to drought, and gave higher yields than Inpari 10, Inpari 1, Silugonggo, and Dodokan. Under drought stress conditions, when the drought conditions were not extreme with soil moistures of 41.3% to 51.7%, yields of the three genotypes were not significantly tolerances from those under the normal condition (6.66 to 7.27 t/ha). Besides drought tolerant, genotypes AS996 and OM5240 were also efficient in using water during the crop growth.